Cross-species amplification of microsatellite DNA markers and comparison on the sequence of microsatellite regions among Southeast Asian Catfish species - Fitri, Muhammad; Siraj, Siti Shapor; Nakajima, Masamichi (The Japanese Society of Fish Genetics and Breeding Science, 2015)
Thirty microsatellite markers developed for River catfish (Hemibagrus nemurus) were screened for cross amplification in six species of catfish. Out of 30 primers, only 3 (10) to 6 (20) produced successful amplifications in six catfish species. Six different loci could be amplified in Pangasius pangasius and Clarias batrachus, 5 loci in Clarias gariepinus, 4 loci in Pseudomystus siamensis and 3 loci in Clarias macrocephalus and Pangasius nasutus. The low rate of amplification in these 6 closely related species proved the primers are locus-specific. Sequence analysis of locus MnRm7-1 showed differences in the flanking region and repeat motif in certain species, suggesting the existence of indel mutations in catfish species in that particular region. The examined DNA sequence revealed that the repeat motif is conser ved within Pangasiid catfishes and not conser ved within Clariid catfishes